Chemical methods to synthesize FeTiO3 powders - Mona, J.; Kale, Sangeeta N.; Gaikwad, A. B.; Murugan, A. Vadivel; Ravi, V. (Materials Letters, 2006)
Three different techniques were used to synthesize FeTiO3 powders. The first method is simple coprecipitation of both Fe and Ti ions under basic conditions using standard ammonia solution from aqueous ferric nitrate and titanium oxy chloride. This precipitate on heating at 400 degrees C produces ilmenite phase. The second method is to digest hydroxide precipitates at 100 degrees C to form FeTiO3 phase. The third technique is to make use of citrate process to form FeTiO3 powders. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). Particle size and morphology were studied by Transmission Electron Microscopy (TEM). (c) 2005 Elsevier B.V. All tights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray methods

Low temperature route to prepare LaMnO3 - Daundkar, A.; Kale, Sangeeta N.; Gokhale, Suresh P.; Ravi, V (Materials Letters, 2006)
A combination of digestion and further low temperature calcination to crystallize the product is employed to prepare LaMnO3(LM) ceramics. Freshly co-precipitated lanthanum and manganese hydroxides gel is allowed to react at 100 degrees C under refluxing and stirring conditions for 6-12 h. The X-ray amorphous product so formed is heated at 300 degrees C to form crystalline LM powders. This is the lowest temperature so far reported for the formation of LaMnO3. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for the calcined powders. (c) 2005 Elsevier B.V All rights reserved.
Keywords: Chemical synthesis; LaMnO3; Precipitation; transmission electron microscopy; X-ray diffraction